Flexural cracking performance of strain-hardening cementitious composites with polyvinyl alcohol: Experimental and analytical study. (30th June 2020) - Bai, Ru; Liu, Shuguang; Yan, Changwang; Zhang, Ju; Wang, Xiaoxiao
Highlights: The maximum crack width of PVA-SHCC beam did not exceed 0.1 mm. PVA-SHCC beam has the characteristic of multiple cracks under flexural load. A calculation model for the stress of steel bars was established. The change of neutral axis height was considered in calculation of crack spacing. A calculation model for crack width of PVA-SHCC beam was proposed. Abstract: A strain-hardening cementitious composite with polyvinyl alcohol (PVA-SHCC) has the characteristic of multiple cracks under tensile load. PVA-SHCC has been utilized to replace ordinary concrete material in this study with the PVA fiber volume as a variation. Five PVA-SHCC and two reinforced concrete (RC) beams were designed to investigate cracking performance under concentrated loads (including crack number, width, spacing, and height). Results of the serviceability limit state showed that cracks on PVA-SHCC beams with fiber volume ratio of 2% were densely distributed, and the maximum crack width did not exceed 0.1 mm. Compared with the RC beams, crack height was reduced by 21.6%−30.9%, and the average crack spacing was reduced by approximately 60%. After the PVA-SHCC beam cracked, the strain on the steel bars did not increase immediately, and the steel bars were considerably coordinated with the deformation of the PVA-SHCC. The reason for this phenomenon is that the addition of randomly distributed PVA fibers effectively limited the expansion of cracks. Given the tensile strain hardening characteristics of PVA-SHCC, the formula for calculating the average crack width of the PVA-SHCC beam is proposed, which can be used for analysis and verification of the crack width of PVA-SHCC beams.